Simultaneous determination of carbaryl and 1-naphthol by first-derivative synchronous non-protected room temperature phosphorescence - Machicote, Roberta Grisel (2009)
The applicability of non-protected room temperature phosphorescence (NP-RTP) in real samples was demonstrated in the present work. In this methodology, only two reagents, potassium iodide and sodium sulfite, were used to obtain phosphorescent signals. Overlapping of the phosphorescence spectra was resolved by using first-derivative synchronous phosphorimetry. The synchronous first-derivative spectra of carbaryl and 1-naphthol in the mixture were completely separated by changing the synchronous wavelength interval; with 240 nm the first-derivative spectra of carbaryl were recorded, while with 200 nm those of 1-naphthol appeared. The intensities in the spectra were proportional to the concentration of carbaryl and 1-naphthol. The calibration graphs were linear up to at least 1.1 × 10 -5 mol L -1 for carbaryl and 1.3 × 10 -5 mol L -1 for 1-naphthol, and the correlation coefficients were 0.9971 and 0.9932, respectively. Carbaryl and 1-naphthol were successfully determined by the proposed method in a hydrolyzed sample of a commercial formulation.